Non-parental caregivers, low maternal education, gastrointestinal problems and high blood lead level: predictors related to the severity of autism spectrum disorder in Northeast China - Han-Yu Dong; Jun-Yan Feng; Hong-Hua Li; Xiao-Jing Yue; Fei-Yong Jia (BMC, 2022)
Abstract Background The prevalence of autism spectrum disorder (ASD) has increased rapidly in recent years. Environmental factors may play an important role in the pathogenesis of ASD. These factors may include socioeconomic factors, nutritional factors, heavy metal exposure, air pollution, etc. Our aim is to analyze possible environmental factors associated with the severity of ASD. Methods All participating children were divided into two groups (mild and moderate/severe) according to the severity of their symptoms, as determined by their Childhood Autism Rating Scale (CARS) scores. The socioeconomic, demographic factors and the nutritional factors that may affect the severity of ASD were included in the logistic regression to analyze whether they were predictors that affected the severity of ASD. Results Logistic regression showed that caregivers(P = 0.042), maternal education (P = 0.030), gastrointestinal problems (P = 0.041) and a high serum concentration of lead (P = 0.003) were statistically significantly associated with ASD severity. Conclusion Many environmental factors affect the severity of ASD. We concluded that non-parental caregivers, low maternal education, gastrointestinal problems and high blood lead level maybe predictors that affected the severity of ASD in northeast China.